Implementation of Criminal Sanctions for Prospection of Newspapers Reviewed From the Book of Criminal Law - Steven Johan (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
The practical purpose of writing this journal is to find out whether the act of spreading newspaper news can be accounted for by its actions in terms of the Criminal Code. In this case it is not appropriate to be charged article 310 of the Criminal Code because the core of article 310 of the Criminal Code is that the product used to defame must be made by the person himself while the news from the newspaper is not a homemade result. If seen in Article 311 of the Criminal Code concerning criminal acts of defamation, the element is fulfilled.